Beyond boundaries: The present and future of 4E cognitive science in interdisciplinary academia, industry, and everyday life. (June 2023) - Tavassoli, Samira; Montoya, Morgan; Ishihara, Ken
What gives a scientific framework a place among laypeople? Can cognitive science change human livelihood? How can cognitive science research extend beyond the bounds of its own field to change academia and society? These are precisely the kinds of questions the 2022 Workshop on "Challenges in 4E Cognition and the Opportunities They Present" sought to address. The workshop gathered an interdisciplinary cohort of researchers from philosophy, psychology, cognitive science, neuroscience, and artificial intelligence to discuss the future of 4E (embodied, embedded, enacted, and extended) cognition research in and outside of Japan. The aim was to identify the most prominent fields in which 4E research is taking place, such as 4E in relation to artificial life, human–computer interfaces, and phenomenology. We strived to articulate the most important open questions in these fields, and understand how adopting a 4E perspective may yield unique ways of answering them, as well as novel avenues of long-term interdisciplinary collaboration. We then discussed how the 4E framework may embed itself as a point of connection between the social and biological sciences, and bridge the gap between academia, medicine, and policymaking, to inform how humans conduct research, think about ourselves, and live life. In this report, we summarize the topics of discussion, the insights garnered, and the practical methods used to ignite discussions and collaborations amongst the researchers in attendance, as a model for future workshops with similar aims.